Health education and medical screening for community well-being in Sriwedari Village - Indah Tri Lestari; Nurul Marfu’ah; Nadia Iha Fatihah; Yulisa Raras Dewi; A’rifa Syukria; Sakhiya Mufida (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Eid al-Adha is a religious moment closely associated with the ritual slaughter of sacrificial animals and an increase in red meat consumption among the community. Although it carries profound religious and social values, excessive consumption may increase the risk of non-communicable diseases (NCDs) if not balanced with a healthy lifestyle. Based on this phenomenon, a community service program was carried out in Sriwedari Village, RT 03/RW 04, Karanganyar Subdistrict, Ngawi Regency, East Java, aiming to raise community awareness of the importance of early detection and prevention of NCDs. The program methods included health education through lectures and discussions, followed by medical screening of blood pressure, random blood glucose levels, and cholesterol. The results showed that 62 percent of residents experienced hypertension, 18 percent had high cholesterol, while the majority of blood glucose levels were within normal limits. Tangible benefits for the community were reflected in the increased awareness to conduct regular health check-ups, improve red meat consumption patterns, and support nutritional fulfillment for vulnerable groups. Furthermore, this program has the potential for sustainability through collaboration between universities, community health centers (puskesmas), and village governments as supporting partners.